Characteristics of Primary Stabbing Headache in a Tertiary Neurological Clinic in China. Issue 5 (7th February 2014) - Liang, Xiping; Ying, Guomin; Huang, Qingqing; Wang, Jing; Li, Nan; Tan, Ge; Zhang, Tristan R.; Huang, Zhen; Zhou, Jiying
Abstract Objectives The aim of this study was to investigate the clinical characteristics of primary stabbing headache (PSH) and its prevalence in a neurology outpatient center at a university hospital in China. Methods We surveyed patients via face‐to‐face interviews by physicians using a questionnaire for headache. Results Of 1, 219 participating patients with headache, 18 (1.5%) were diagnosed with PSH. The mean age was 44.1 ± 15.5 years. The headaches were localized to a single fixed area in 61.1% of patients. The frontal cerebral regions were reported as most common areas. Fourteen patients (77.8%) suffered from moderate to severe intensity headache with a mean score of 4.3 ± 1.9 on an 11‐point pain scale. Of the patients, 27.8% had accompanying symptoms with photophobia/phonophobia as the most common complaint(s). Fifty percent of patients reported trigger factors, with weather change noted as a common trigger. Conclusion PSH was shown to have an onset at middle age with moderate‐to‐severe intensity attacks localized predominantly within the first division of the trigeminal nerve. Accompanying phenomena and trigger factors were common and should be noted, implying further research to be conducted.